VetCAST Method for Determination of the Pharmacokinetic-Pharmacodynamic Cut-Off Values of a Long-Acting Formulation of Florfenicol to Support Clinical Breakpoints for Florfenicol Antimicrobial Susceptibility Testing in Cattle - Toutain, Pierre-Louis; Sidhu, Pritam Kaur; Lees, Peter; Rassouli, Ali; Pelligand, Ludovic (Frontiers in Microbiology, 2019)
The PK/PD cut-off (PK/PDCO ) value of florfenicol for calf pathogens was determined for long acting formulations (MSD Nuflor® and a bioequivalent generic product). PK/PDCO is one of the three MICs considered by VetCAST, a sub-committee of the European Committee on Susceptibility Testing, to establish a Clinical Breakpoint for interpreting Antimicrobial Susceptibility Testing. A population model was built by pooling three pharmacokinetic data sets, obtained from 50 richly sampled calves, receiving one of two formulations (the pioneer product and a generic formulation). A virtual population of 5000 florfenicol disposition curves was generated by Monte Carlo Simulations over the 96 h of the assumed duration of action of the formulations. From this population, the maximum predicted MIC, for which 90% of calves can achieve some a priori selected critical value for two PK/PD indices, AUC/MIC and T>MIC, was established. Numerical values were established for two bacterial species of the bovine respiratory disease complex, Pasteurella multocida and Mannheimia haemolytica. It was concluded that the PK/PDCO of florfenicol for both AUC/MIC and T>MIC was 1 mg/L.